Sistematización de un proyecto de educación en valores - Redondo Duarte, Sara; Navarro Asencio, Enrique (Revista Complutense de Educación, 2007)
This paper is part of an educational innovation project called “Other world is possible, other world is necessary”. The project was implemented in a high school in Madrid and it deals with values education. All the educational community was involved in the project. The aim of this study was to discover those factors that induce teachers to participate in this kind of project. Two instruments were used in order to collect the information: a questionnaire applied to all the teachers involved in the project and an interview for certain teachers belonging to three Teaching Departments and with different levels of involvement in the project. The framework of this study is a methodology called Systematization.
Keywords: Values education; Systematization; Teachers